2013
DOI: 10.1016/j.ydbio.2013.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Shadow enhancers flanking the HoxB cluster direct dynamic Hox expression in early heart and endoderm development

Abstract: The products of Hox genes function in assigning positional identity along the anterior-posterior body axis during animal development. In mouse embryos, Hox genes located at the 3' end of HoxA and HoxB complexes are expressed in nested patterns in the progenitors of the secondary heart field during early cardiogenesis and the combined activities of both of these clusters are required for proper looping of the heart. Using Hox bacterial artificial chromosomes (BACs), transposon reporters, and transgenic analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 62 publications
0
45
0
Order By: Relevance
“…Mammals retain Nppa and Nppb, conserved among species and positioned at a distance of only 15 kb from each other in the genome (Inoue et al, 2003). Several studies of clustered genes describe coordinated regulation by shared regulatory sequences (Nolte et al, 2013;Tena et al, 2011). Given the highly similar spatiotemporal expression patterns of Nppa and Nppb, we hypothesized that these clustered genes might also share regulatory elements.…”
Section: Discussion the Nppa-nppb Cluster Is Confined To A Regulatorymentioning
confidence: 98%
See 1 more Smart Citation
“…Mammals retain Nppa and Nppb, conserved among species and positioned at a distance of only 15 kb from each other in the genome (Inoue et al, 2003). Several studies of clustered genes describe coordinated regulation by shared regulatory sequences (Nolte et al, 2013;Tena et al, 2011). Given the highly similar spatiotemporal expression patterns of Nppa and Nppb, we hypothesized that these clustered genes might also share regulatory elements.…”
Section: Discussion the Nppa-nppb Cluster Is Confined To A Regulatorymentioning
confidence: 98%
“…They are positioned at 10 to 15 kb distance from each other in the mammalian genome. Analysis of other gene clusters, such as Iroquois and Hox, revealed that multiple genes within a cluster have similar expression patterns and are regulated by shared regulatory sequences (Nolte et al, 2013;Tena et al, 2011). These features may underlie the evolutionary stability of such clusters.…”
Section: Introductionmentioning
confidence: 97%
“…RA is able to shift the expression pattern of Hox genes in the pharyngeal mesoderm [11,94,98,99] and thus it is likely that RA can also regulate Hox expression in the pharyngeal endoderm [101]. Hox genes are known to vary in response to different concentrations of RA in many tissues and reporter assays for RA activity suggest that such a gradient of RA signaling exists in the pharyngeal endoderm [53,99,104].…”
Section: Retinoic Acid and The Pharynxmentioning
confidence: 99%
“…Subdivision of the Cdx expression domain into different regions such as the large and small intestine correspond to expression of different members of the Hox gene cluster and it is likely that these are essential for defining the different fates as mutations in different Hox genes do cause gut malformations [130]. Given the essential role for RA in directly regulating the Hox gene cluster [104,135], it would appear likely that subdivision of the hindgut would be regulated, at least in part, by RA.…”
Section: Retinoic Acid and Posterior Endodermmentioning
confidence: 99%
“…Interestingly, we also observed derepression of yR7 enh in outer PRs in dve mutants, suggesting that yR7 enh serves as an inducible backup or 'dark' shadow enhancer in these cells. Shadow enhancers are DNA elements that drive redundant expression patterns and ensure robust gene expression in cases of genetic and environmental perturbation (Bothma et al, 2015;Frankel et al, 2010;Hong et al, 2008;Miller et al, 2014;Nolte et al, 2013;Perry et al, 2010;Wunderlich et al, 2015). yR7 enh represents an unusual 'dark' shadow enhancer as it is normally repressed and only becomes active when Dve driven by the primary outer enh is compromised.…”
Section: Introductionmentioning
confidence: 99%